Guide to design a strategic marketing plan to increase professional women in information technologies - Rodríguez-Rodríguez, Nadia Katherine (2017)
This work seeks to show the situation of an undergraduate career related to information technologies and the low population of women among its students; in contrast to the great job opportunities and social mobility offered by this career, both locally and internationally. Indeed, today’s companies require professionals of careers linked to information technologies, and, moreover, seek diversity among their collaborators. This paper also aims to create a conceptual framework related to a marketing strategy and a methodology for the elaboration of a strategic marketing plan in order to increase the number of women in these careers. And also, to contribute to the gender balance in information technologies careers in Peru.